Implementasi Aplikasi KBM Sebagai Media Pembelajaran Menulis Cerpen Siswa MTs Al-Amiriyyah Darussalam Banyuwangi - Fina Zaidatul Istiqomah; Abdul Rani (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
The use of learning media makes it easier for teachers to convey the learning process. New and easy media can stimulate students to produce maximum learning results. This research aims to: 1) Describe the short story writing abilities of class IX students at MTs Al-Amiriiyah Darussalam Blokagung Banyuwangi. 2) Describe the process of writing short stories using the KBM application for class IX students at MTs Al-Amiriiyah Darussalam Blokagung Banyuwangi. The research method used is qualitative with a case study approach. Data collection techniques used were observation, interviews and documentation. Meanwhile, the data analysis used is the Interactive Model of Milles and Hubarman, including: data collection, data reduction, data presentation, and drawing conclusions. The validity of the data used is a triangulation. of methods, techniques and theories. The results of this research are that the abilities of class IX students at MTs Al-Amiriiyah Darussalam Blokagung Banyuwangi are very good. This can be seen from the results of the short stories written. Starting from determining intrinsic and extrinsic elements, generating problems and solving short story problems. The use of learning media makes it easier for teachers to deliver the learning process. New and easy media can stimulate students in producing maximum learning results. as well as the use of learning media to write short stories using the KBM application. This study aims to: 1) Describe the application of KBM application as a. learning medium for writing short stories for grade IX MTs Al-Amiriiyah Darussalam Blokagung Banyuwangi students. 2) Disadvantages and advantages of ascetics.